Electrode and preparation method thereof, secondary battery, battery module, battery pack and power-consuming device

By adding lithium supplement agent to the secondary battery electrode to form an appropriate active material layer structure, the problem of difficult to take into account both the energy density and ion diffusion kinetics in the prior art is solved, and the battery performance with high energy density and high kinetics is achieved .

CN115832187BActive Publication Date: 2025-02-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210850703.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-20
Publication Date
2025-02-18
Estimated Expiration
2042-07-20

AI Technical Summary

Technical Problem

While the prior art increases the energy density of secondary batteries, it is difficult to meet the demand for high ion diffusion kinetics, resulting in limited battery performance.

Method used

By adding lithium supplement agent to the preparation process of the electrode, the first active material layer and the second active material layer are formed, and the porosity and compaction density are adjusted respectively to improve the ion diffusion kinetics and energy density of the electrode.

Benefits of technology

The secondary battery can meet the needs of high energy density and high ion diffusion kinetics, and improve the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115832187B_ABST
    Figure CN115832187B_ABST
Patent Text Reader

Abstract

The present application provides an electrode and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electric device, wherein the electrode comprises: a current collector; a first active material layer, located on at least one surface of the current collector, the porosity of the first active material layer is 15% to 30%, and the pores in the first active material layer are formed by a lithium supplement; a second active material layer, located on the surface of the first active material layer away from the current collector, and the compaction density of the second active material layer is 2.2g / cc to 3.7g / cc. The electrode has high energy density and ion diffusion kinetics; the above-mentioned electrode is applied to a secondary battery, which can enable the secondary battery to simultaneously meet the requirements of high energy density and high ion diffusion kinetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an electrode and a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. With the continuous development of the new energy industry, customers have put forward higher requirements for the use of secondary batteries, such as high energy density.

[0003] In the related art, the energy density of the battery is often improved by increasing the electrode thickness, but increasing the electrode thickness also leads to poor ion diffusion kinetics of the battery; that is, in the related art, increasing the electrode thickness cannot simultaneously meet high energy density and high ion diffusion kinetics. Summary of the invention

[0004] Based on this, it is necessary to provide electrodes and preparation methods thereof, secondary batteries, battery modules, battery packs and electrical devices, so that the secondary batteries can simultaneously meet the requirements of high energy density and high ion diffusion kinetics.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides an electrode, comprising:

[0006] current collector;

[0007] A first active material layer, located on at least one surface of the current collector, wherein the porosity of the first active material layer is 15% to 50%, and the pores in the first active material layer are formed by a lithium supplement;

[0008] The second active material layer is located on a surface of the first active material layer away from the current collector, and the compaction density of the second active material layer is 2.2 g / cc to 3.7 g / cc.

[0009] The electrode of the present application is prepared by adding a lithium supplement when preparing the electrode. The lithium supplement releases lithium ions and produces oxygen during the high voltage formation process. The released lithium ions can increase the lithium salt concentration in the electrolyte, increase the ionic conductivity of the electrolyte, and enhance the power of lithium ions to migrate into the electrode; oxygen forms pores in the first active material layer, and the porosity is as high as 15% to 50%. On the one hand, the higher porosity is conducive to electrolyte infiltration and ion diffusion, reduces the electrode concentration polarization effect, and improves the ion dynamics of the electrode; on the other hand, the higher porosity is conducive to the transfer of electrons in the second active material layer away from the current collector to the current collector, shortens the transfer path, reduces resistance, and improves the ion diffusion dynamics of the electrode; at the same time, the compaction density of the second active material layer is controlled to be as high as 2.2g / cc to 3.7g / cc, thereby improving the energy density of the electrode. In this way, the above-mentioned electrode is applied to secondary batteries, which can enable the secondary batteries to meet the requirements of high energy density and high ion diffusion dynamics at the same time.

[0010] In some embodiments, the resistance of the first active material layer is denoted as R1, the resistance of the second active material layer is denoted as R2, and then 1.0≤R1 / R2≤3.0.

[0011] In some embodiments, the resistance of the first active material layer satisfies: 0.8Ω≤R1≤3.0Ω, and the resistance of the second active material layer satisfies: 0.3Ω≤R2≤1.0Ω.

[0012] In some embodiments, the porosity of the second active material layer is 5% to 20%.

[0013] In some embodiments, the second active material layer includes a second active material, the second active material includes particles of a first particle size and particles of a second particle size, the volume average particle size Dv50 of the particles of the first particle size is denoted as D1, and the volume average particle size Dv50 of the particles of the second particle size is denoted as D2, then the volume average particle size Dv50 of the particles of the first particle size satisfies: 10μm≤D1≤20μm, and the volume average particle size Dv50 of the particles of the second particle size satisfies: 0.5μm≤D2<10μm.

[0014] In some embodiments, the mass proportion of the particles with the first particle size in the second active material is 60% to 90%, and the mass proportion of the particles with the second particle size in the second active material is 10% to 40%.

[0015] In some embodiments, the second active material includes one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, and graphene.

[0016] In some embodiments, the total thickness of the first active material layer and the second active material layer is 80 to 300 μm;

[0017] Optionally, the thickness of the first active material layer accounts for 10% to 60% of the total thickness of the first active material layer and the second active material layer.

[0018] In some embodiments, the lithium supplement includes one or more of lithium oxide, lithium superoxide, and lithium-rich transition metal oxide;

[0019] Optionally, the lithium-rich transition metal oxide includes Li 2 NiO 2 , Li 5 FeO 4 , Li 2 MnO 3 , Li 6 CoO 4 , Li 6 MnO 4 Li 6 R 4 One or more of .

[0020] The second aspect of the present application provides a method for preparing an electrode, comprising the following steps:

[0021] preparing a first slurry, wherein the first slurry includes a first active material and a lithium supplement;

[0022] coating the lithium supplement agent on at least one surface of the current collector to form a first active material layer;

[0023] A second slurry is prepared, and the second slurry is coated on a surface of the first active material layer away from the current collector to form a second active material layer.

[0024] In some embodiments, the amount of the lithium supplement agent added accounts for 1% to 10% of the total mass of the first active material and the lithium supplement agent.

[0025] In some embodiments, the volume average particle size Dv50 of the first active substance is recorded as D3, and the volume average particle size Dv50 of the lithium supplement is recorded as D4. Then the volume average particle size Dv50 of the first active substance satisfies: 0.5μm≤D3≤20μm, and the volume average particle size Dv50 of the lithium supplement satisfies: 1μm≤D4≤10μm.

[0026] In some embodiments, the lithium supplement includes one or more of lithium oxide, lithium superoxide, and lithium-rich transition metal oxide;

[0027] Optionally, the lithium-rich transition metal oxide includes Li 2 NiO 2 , Li 5 FeO4 , Li 2 MnO 3 , Li 6 CoO 4 , Li 6 MnO 4 Li 6 R 4 One or more of .

[0028] A third aspect of the present application provides a secondary battery, which includes a positive electrode plate, wherein the positive electrode plate is the electrode described above in the present application or an electrode prepared by the method described above in the present application.

[0029] A fourth aspect of the present application provides a battery module, which includes the secondary battery of the third aspect of the present application.

[0030] A fifth aspect of the present application provides a battery pack, which includes the battery module of the fourth aspect of the present application.

[0031] The sixth aspect of the present application provides an electrical device, which includes one or more of the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, and the battery pack of the fifth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0033] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0034] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0035] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0036] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0037] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0038] Description of reference numerals:

[0039] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly; 6 electrical device. DETAILED DESCRIPTION

[0040] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0043] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0044] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0045] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0046] High energy density and high kinetics have always been the core requirements of energy storage devices. In the related art, the energy density of the battery is often increased by increasing the thickness of the electrode. Under the same chemical system, the more active materials contained in the electrode with increased thickness, the more energy can be stored accordingly. Increasing the thickness of the electrode is an important method to achieve high energy density batteries. However, in the related art, while increasing the thickness of the electrode to increase the energy density of the battery, it also leads to poor ion diffusion kinetics of the battery. The technicians of this application have found that this is mainly because after the electrode is thickened, it will be more difficult for the electrolyte to infiltrate or the lithium ions to diffuse, especially the active material layer close to the current collector is far away from the electrolyte, and the lithium ion concentration polarization is obvious during the charge and discharge process, resulting in difficulty in the migration of lithium ions in the active material layer close to the current collector, which seriously affects the charge and discharge efficiency; at the same time, the electrons in the active material layer far away from the current collector in the electrode with increased thickness need to pass through a longer path to transfer to the current collector, and the resistance increases, which affects the performance of the battery.

[0047] In order to solve the above problems, the present application provides an electrode, comprising:

[0048] current collector;

[0049] The first active material layer is located on at least one surface of the current collector, the porosity of the first active material layer is 15% to 50%, and the pores in the first active material layer are formed by the lithium supplement

[0050] The second active material layer is located on the surface of the first active material layer away from the current collector, and the compaction density of the second active material layer is 2.2g / cc to 3.7g / cc. The electrode of the present application is prepared by adding a lithium supplement when the electrode is prepared. The lithium supplement releases lithium ions and generates oxygen during the high voltage formation process. The released lithium ions can increase the concentration of lithium salts in the electrolyte, increase the ionic conductivity of the electrolyte, and enhance the power of lithium ions to migrate into the electrode; oxygen forms pores in the first active material layer, and the porosity is as high as 15% to 50%. On the one hand, the higher porosity is conducive to electrolyte infiltration and ion diffusion, reduces the electrode concentration polarization effect, and improves the ion dynamics of the electrode; on the other hand, the higher porosity is conducive to the transfer of electrons in the second active material layer away from the current collector to the current collector, shortens the transfer path, reduces resistance, and improves the ion diffusion dynamics of the electrode; at the same time, the compaction density of the second active material layer is controlled to be as high as 2.2g / cc to 3.7g / cc, thereby improving the energy density of the electrode. The above-mentioned electrode is applied to a secondary battery, so that the secondary battery can simultaneously meet the requirements of high energy density and high ion diffusion kinetics.

[0051] The porosity of the first active material layer mentioned above is measured by the following method:

[0052] Disassemble the formed secondary battery to obtain the formed electrode sheet, scrape off the second active material layer of the electrode sheet, take the electrode sheet coated with the first active material layer, use a sheet puncher to punch out small discs with a diameter of 14 mm, and use tweezers to select more than 20 discs with good appearance and no powder falling on the edges and put them into the sample cup. Record the number of discs and calculate the apparent volume V2. Place the sample cup with the discs in a true density tester, a closed test system, and introduce helium according to the procedure. By detecting the pressure of the gas in the sample chamber and the expansion chamber, the real volume V1 is calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested. Porosity P=(V2-V1) / V2*100%, apparent volume V2=S*H*A;

[0053] Where S represents the area, cm 2 ; H is the thickness, cm; A is the number of electrode discs; V1 is the actual volume of the disc, cm 3 ; V2 is the apparent volume of the electrode disc, cm 3 .

[0054] The compaction density refers to the mass of active material per unit volume of the electrode, which can be calculated using the ratio of coating surface density to coating thickness. It is one of the important reference indicators for the energy density of the electrode. The compaction density of the second active material layer mentioned above is tested by the following method: determine the coating surface density of the second active material layer according to the energy density design requirements; use a vernier caliper to measure the total thickness of the electrode, deduct the thickness of the current collector and the first active material layer to calculate the thickness of the second active material layer; calculate the compaction density of the second active material layer based on the two parameters of coating surface density and coating thickness.

[0055] The porosity of the first active material layer provided in the embodiment of the present application is 15% to 50%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc. Further, the porosity of the first active material layer is 20% to 40%. Furthermore, the porosity of the first active material layer is 25%.

[0056] The compacted density of the second active material layer provided in the embodiment of the present application is 2.2 g / cc to 3.7 g / cc, for example, it can be 2.2 g / cc, 2.5 g / cc, 2.7 g / cc, 3.0 g / cc, 3.3 g / cc, 3.5 g / cc or 3.7 g / cc, etc. Further, the compacted density of the second active material layer is 3.4 g / cc to 3.7 g / cc. Furthermore, the compacted density of the second active material layer is 3.6 g / cc.

[0057] As an example, the current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0058] The applicant has found through in-depth research that when the electrode of the present application satisfies the above-mentioned design conditions and optionally satisfies one or more of the following conditions, the performance of the secondary battery can be further improved.

[0059] In some embodiments, the resistance of the first active material layer is recorded as R1, and the resistance of the second active material layer is recorded as R2, then 1.0≤R1 / R2≤3.0. If the resistance of the first active material layer is greater than the resistance of the second active material layer, then the conductivity of the second active material layer is greater than the resistivity of the first active material layer, which is beneficial to improve the electron transfer in the second active material layer away from the current collector and realize the rapid insertion and extraction of lithium ions. Further, R1 / R2 is 1.67.

[0060] In some embodiments, the resistance of the first active material layer satisfies: 0.8Ω≤R1≤3.0Ω, further, 0.8Ω≤R1≤1.5Ω; the resistance of the second active material layer satisfies: 0.3Ω≤R2≤1.0Ω, further, 0.5Ω≤R2≤1.0Ω.

[0061] The resistance of the first active material layer mentioned above is tested by the following method: scrape off the second active material layer of the electrode, retain the first active material layer, cut the film after rolling the electrode into a rectangular size of about 5cm×10cm, place it between the two electrodes of the film resistance meter, set the test pressure and holding time parameters on the built-in software, start the test, and the software automatically reads the film thickness, resistance, resistivity, conductivity and other data. Randomly select 10 positions for each film for testing, and calculate the average value R1.

[0062] The resistance of the second active material layer mentioned above is tested in the following way: cut the film after rolling the pole piece into a rectangular size of about 5cm×10cm, place it between the two electrodes of the film resistance meter, set the test pressure and holding time parameters on the built-in software, start the test, and the software automatically reads the film thickness, resistance, resistivity, conductivity and other data. 10 positions are randomly selected for each film for testing, and the average value R 总 , R 2 =R 总 -R1 .

[0063] In some embodiments, the porosity of the second active material layer is 5% to 20%.

[0064] The porosity of the second active material layer mentioned above is tested by the following method: take the electrode sheet coated with the second active material layer, use a sheet puncher to punch out small discs with a diameter of 14 mm, and use tweezers to select more than 20 discs with good appearance and no powder falling on the edges and put them into the sample cup. Record the number of discs and calculate the apparent volume V2. Place the sample cup containing the discs in a vacuum density tester and a closed test system. Helium is introduced according to the procedure. The pressure of the gas in the sample chamber and the expansion chamber is detected, and the real volume V1 is calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested. Porosity P=(V2-V1) / V2*100%, apparent volume V2=S*H*A;

[0065] Where S represents the area, cm 2 ; H is the thickness, cm; A is the number of electrode discs; V1 is the actual volume of the disc, cm 3 ; V2 is the apparent volume of the electrode disc, cm 3 .

[0066] In some embodiments, the second active material layer includes a second active material, the second active material includes particles of a first particle size and particles of a second particle size, the volume average particle size Dv50 of the particles of the first particle size is denoted as D1, and the volume average particle size Dv50 of the particles of the second particle size is denoted as D2, then the volume average particle size Dv50 of the particles of the first particle size satisfies: 10μm≤D1≤20μm, further: 15μm≤D1≤20μm; the volume average particle size Dv50 of the particles of the second particle size satisfies: 0.5μm≤D2<10μm, further, 5μm≤D2≤9μm.

[0067] It should be noted that the volume average particle size Dv50 refers to the particle size corresponding to 50% of the cumulative particle size distribution number in the volume cumulative distribution curve. Its physical meaning is that particles with a particle size smaller than (or larger than) it account for 50%. As an example, Dv50 can be conveniently measured by a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.

[0068] In some embodiments, the mass proportion of the first particle size particles in the second active material is 60% to 90%, and the mass proportion of the second particle size particles in the second active material is 10% to 40%. For example, the mass proportion of the first particle size particles in the second active material can be 60%, 70%, 80% or 90%, etc., and correspondingly, the mass proportion of the second particle size particles in the second active material layer can be 40%, 30%, 20% or 10%, etc. Further, the mass proportion of the first particle size particles in the second active material is 60% to 75%, and the mass proportion of the second particle size particles in the second active material is 25% to 40%.

[0069] It can be understood that the use of first particle size particles with a larger particle size is beneficial to increasing the porosity of the second active material layer, and the use of second particle size particles with a smaller particle size is beneficial to increasing the compaction density of the second active material layer. The combination of first particle size particles and second particle size particles can make the second active material layer have a high compaction density and a suitable porosity.

[0070] In some embodiments, the second active material layer includes one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene. Single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene have strong electrical conductivity, which is beneficial to improving the capacity and energy density of the secondary battery.

[0071] In some embodiments, the total thickness of the first active material layer and the second active material layer is 80-300 μm; for example, it can be 80 μm, 100 μm, 150 μm, 500 μm, 250 μm or 300 μm, etc. Optionally, the total thickness of the first active material layer and the second active material layer is 80-100 μm.

[0072] Further, the thickness of the first active material layer accounts for 10% to 60% of the total thickness of the first active material layer and the second active material layer; for example, it can be 10%, 20%, 30%, 40%, 50% or 60%, etc.; further, the thickness of the first active material layer accounts for 20% to 60% of the total thickness of the first active material layer and the second active material layer. The pores in the first active material layer can be made by lithium supplementation, which can improve the kinetic performance, but the pores themselves reduce the energy density of the battery. Therefore, the thickness of the first active material layer will have an important influence on the kinetics and overall energy density of the battery. If the first active layer is too thick, the kinetics will be improved, but the energy density will be seriously lost; if the first active material layer is too thin, the energy density will be high, but the kinetic improvement effect will be insufficient.

[0073] The total thickness of the first active material layer and the second active material layer mentioned above and the proportion of the first active material layer in the total thickness are tested by the following method: perform cross-sectional CP characterization on the electrode, measure the thickness L1 of the first active material layer and the thickness L2 of the second negative electrode active material layer, then the total thickness L of the first active material layer and the second active material layer is: L=L1+L2, and the proportion of the first active material layer in the total thickness is: L1 / L*100%.

[0074] In some embodiments, the lithium supplement includes one or more of lithium oxide, lithium superoxide and lithium-rich transition metal oxide; optionally, the lithium-rich transition metal oxide includes Li 2 NiO 2 , Li 5 FeO 4 , Li 2 MnO 3 , Li 6 CoO 4 , Li 6 MnO 4 Li 6 R 4 One or more of .

[0075] The present application also provides a method for preparing an electrode, comprising the following steps:

[0076] preparing a first slurry, wherein the first slurry includes a first active material and a lithium supplement;

[0077] coating a lithium supplement agent on at least one surface of a current collector to form a first active material layer;

[0078] A second slurry is prepared and coated on a surface of the first active material layer away from the current collector to form a second active material layer.

[0079] When preparing the electrode in the present application, a lithium supplement agent is added to the first slurry. The lithium supplement agent releases lithium ions and generates oxygen during the high-voltage formation process. The released lithium ions can increase the lithium salt concentration in the electrolyte and the ionic conductivity of the electrolyte, thereby increasing the power for lithium ions to migrate into the interior of the electrode. Oxygen forms pores in the first active material layer, increasing the porosity of the first active material layer, and oxygen can be discharged from the battery cell during the formation and aging process.

[0080] In some embodiments, the amount of the lithium supplement agent added accounts for 1% to 10% of the total mass of the first active material and the lithium supplement agent; for example, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. It is understood that by adjusting the amount of the lithium supplement agent added, the porosity size in the first active material layer after formation can be adjusted. Furthermore, the amount of the lithium supplement agent added accounts for 5% to 10% of the total mass of the first active material and the lithium supplement agent.

[0081] In some of the embodiments, the volume average particle size Dv50 of the first active material is recorded as D3, and the volume average particle size Dv50 of the lithium supplement is recorded as D4. Then the volume average particle size Dv50 of the first active material satisfies: 0.5μm≤D3≤20μm; further, 10μm≤D3≤20μm. The volume average particle size Dv50 of the lithium supplement satisfies: 1μm≤D4≤10μm; further, 1μm≤D4≤5μm. It can be understood that by adjusting the volume average particle size Dv50 of the lithium supplement, the porosity in the first active material layer after formation can be further adjusted.

[0082] In some embodiments, the lithium supplement includes one or more of lithium oxide, lithium superoxide and lithium-rich transition metal oxide; optionally, the lithium-rich transition metal oxide includes Li 2 NiO 2 , Li 5 FeO 4 , Li 2 MnO 3 , Li 6 CoO 4 , Li 6 MnO 4 Li 6 R 4 One or more of .

[0083] The above raw materials can be obtained from the market unless otherwise specified.

[0084] Secondary battery

[0085] The present application also provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate is the electrode provided above in the present application or an electrode prepared by the method provided above in the present application.

[0086] When the electrode provided above in the present application is used as the positive electrode sheet of a secondary battery, if the secondary battery is a lithium-ion battery, the first active material contained in the first active material layer and the second active material contained in the second active material layer can respectively adopt positive electrode active materials for lithium-ion batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2 O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 (Also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O 2 (Also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O 2 (Also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O 2 (Also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O 2 (Also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O 2 ) and its modified compounds, etc. Examples of lithium phosphates containing olivine structures may include, but are not limited to, lithium iron phosphate (such as LiFePO 4 (also referred to as LFP), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4), at least one of a composite material of lithium manganese phosphate and carbon, a composite material of lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0087] When the electrode provided in the present application is used as the positive electrode of a secondary battery, if the secondary battery is a sodium ion battery, the first active material contained in the first active material layer and the second active material contained in the second active material layer can respectively adopt positive electrode active materials for sodium ion batteries known in the art. As an example, only one positive electrode active material can be used alone, or two or more positive electrode active materials can be combined. Among them, the positive electrode active material can be selected from sodium iron composite oxide (NaFeO 2 ), sodium cobalt composite oxide (NaCoO 2 ), sodium chromium composite oxide (NaCrO 2 ), sodium manganese composite oxide (NaMnO 2 ), sodium nickel composite oxide (NaNiO 2 ), sodium nickel titanium composite oxide (NaNi 1 / 2 Ti 1 / 2 O 2 ), sodium nickel manganese composite oxide (NaNi 1 / 2 Mn 1 / 2 O 2 ), sodium iron manganese composite oxide (Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O 2 ), sodium nickel cobalt manganese composite oxide (NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ), sodium iron phosphate (NaFePO 4 ), sodium manganese phosphate (NaMn P O 4 ), sodium cobalt phosphate (NaCoPO 4 ), Prussian blue materials, polyanion materials (phosphates, fluorophosphates, pyrophosphates, sulfates), etc., but the present application is not limited to these materials. The present application can also use other traditionally known materials that can be used as positive electrode active materials for sodium ion batteries.

[0088] The first active material layer and the second active material layer respectively usually further optionally include a binder and other optional auxiliary agents.

[0089] As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0090] The secondary battery also includes a negative electrode, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode and the negative electrode. The separator is arranged between the positive electrode and the negative electrode to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode and the negative electrode.

[0091] Negative electrode

[0092] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0093] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0094] As an example, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0095] As an example, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. Furthermore, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0096] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0097] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0098] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0099] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0100] Isolation film

[0101] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0102] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0103] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0104] Electrolyte

[0105] The secondary battery may include an electrolyte that conducts ions between the positive electrode and the negative electrode. The electrolyte may include an electrolyte salt and a solvent.

[0106] As an example, the electrolyte salt may be selected from lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2), one or more of lithium difluorooxalate phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).

[0107] As an example, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0108] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0109] In some embodiments, the secondary battery of the present application is a lithium ion secondary battery.

[0110] Secondary batteries can be prepared according to conventional methods in the art, for example, the positive electrode sheet, the separator, and the negative electrode sheet are wound (or stacked) in sequence, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain a battery cell, the battery cell is placed in an outer package, the electrolyte is injected and the package is sealed to obtain a secondary battery.

[0111] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0112] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0113] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0114] In some embodiments, reference Figure 2The outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity.

[0115] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 52. ​​The electrode assembly 52 is encapsulated in the housing cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to needs.

[0116] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0117] Figure 3 The battery module 4 is used as an example. In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0118] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0119] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0120] Figure 4 and Figure 5 The battery pack 1 is taken as an example. The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0121] Electrical devices

[0122] The present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack. The secondary battery, battery module, or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0123] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0124] Figure 6 The power consumption device 6 is taken as an example. The power consumption device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.

[0125] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0126] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.

[0127] Example

[0128] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.

[0129] It should be noted that in the following embodiments and comparative examples, the electrode provided in the present application is used as the positive electrode of the secondary battery.

[0130] The resistance of the first negative electrode active material layer is denoted as R1, the resistance of the second negative electrode active material layer is denoted as R2, the volume average particle size Dv50 of the first particle size particles in the second active material is denoted as D1, the volume average particle size Dv50 of the second particle size particles is denoted as D2, the thickness of the first active material layer is denoted as L1, and the thickness of the second active material layer is L2.

[0131] The materials used in the examples of this application can all be obtained commercially.

[0132] 1. Preparation of positive electrode

[0133] Example 1

[0134] NCM811 (as the first active material), Li 5 FeO 4(as a lithium supplement agent), conductive carbon black, binder PVDF and solvent N-methylpyrrolidone (NMP) are uniformly stirred in a weight ratio of 93:2:2:3:100 to obtain a uniformly mixed first slurry; the first slurry is uniformly coated on an aluminum foil current collector with a thickness of 15 μm to form a first active material layer, and then dried at 110° C.; wherein the amount of the lithium supplement agent added accounts for 2% of the total mass of the first active material and the lithium supplement agent;

[0135] NCM811 (as the second active material), carbon nanotubes (as the conductive agent), binder PVDF and solvent N-methylpyrrolidone (NMP) are uniformly stirred at a weight ratio of 97:1:2:100 to obtain a uniformly mixed second slurry; the second slurry is uniformly coated on the surface of the dried first active material layer to form a second active material layer, and then dried at 110°C, and a positive electrode plate is obtained after a cold pressing process with a pressure of 20-40 tons. Among them, the volume average particle size Dv50 of the first particle size particles in the second active material is 15μm, accounting for 60% by mass, and the volume average particle size Dv50 of the second particle size particles is 5μm, accounting for 40% by mass.

[0136] Example 2-33

[0137] The preparation method of the positive electrode sheet in Example 2-33 is basically the same as the preparation method of the positive electrode sheet in Example 1, and the main difference is: the type of lithium supplement agent, the percentage of the lithium supplement agent in the total mass of the first active material and the lithium supplement agent, the volume average particle size Dv50 and / or mass proportion of the first particle size particles contained in the second active material, the volume average particle size Dv50 and / or mass proportion of the second particle size particles contained in the second active material, the thickness of the first active material layer and the thickness of the second active material layer are different. See Table 1 below for details.

[0138] Comparative Example 1

[0139] The preparation method of the positive electrode sheet in Comparative Example 1 is basically the same as the preparation method of the positive electrode sheet in Example 1, and the main difference is that no lithium supplement agent is added when preparing the first slurry, and the first active material of the same mass is used to replace the lithium supplement agent.

[0140] 2. Positive electrode performance test

[0141] The performance tests of the positive electrode sheets prepared in Examples 1-33 and Comparative Examples 1-2 were performed, including: the thickness L1 and resistance R1 of the first active material layer, the thickness L2, resistance R2 and porosity, compaction density, and volume average particle size Dv50 of the first particle size particles and the second particle size particles in the second active material; the specific method is as follows:

[0142] The test method for the resistance R1 of the first active material layer is as follows: scrape off the second active material layer of the electrode, retain the first active material layer, cut the electrode sheet after rolling into a rectangular size of about 5cm×10cm, place it between the two electrodes of the membrane resistance meter, set the test pressure and holding time parameters on the built-in software, start the test, and the software automatically reads the membrane thickness, resistance, resistivity, conductivity and other data. Randomly select 10 positions for each membrane for testing, and calculate the average value R1.

[0143] The test method for the resistance R2 of the second active material layer is as follows: cut the film after rolling the pole piece into a rectangular size of about 5cm×10cm, place it between the two electrodes of the film resistance meter, set the test pressure and holding time parameters on the built-in software, start the test, and the software automatically reads the film thickness, resistance, resistivity, conductivity and other data. 10 positions are randomly selected for each film for testing, and the average value R 总 , R 2 =R 总 -R 1 .

[0144] The thickness L of the first active material layer 1 and the thickness L of the second active material layer 2 The test method is: perform cross-sectional CP characterization on the electrode and measure the thickness L of the first active material layer. 1 and the thickness L of the second active material layer 2 .

[0145] The porosity of the second active material layer is tested by using the true density method described above to measure the porosity of the entire electrode, then scraping off the second active material layer to measure the porosity of the first active material layer and the porosity of the second active material layer ε 2 =[ε 总 (L 1 +L 2 )-ε 1 L 1 ] / L 2 ; where ε 总 Represents the porosity of the entire electrode, ε 1 represents the porosity of the first active material layer, ε 2 represents the porosity of the second active material layer.

[0146] The testing method for the compaction density of the second active material layer is as follows: determine the coating surface density of the second active material layer according to the energy density design requirements; use a vernier caliper to measure the total thickness of the electrode, deduct the thickness of the current collector and the first active material layer to calculate the thickness of the second active material layer; calculate the compaction density of the second active material layer based on the two parameters of coating surface density and coating thickness.

[0147] The test method for the volume average particle size Dv50 of the first particle size particles and the second particle size particles is: referring to the particle size distribution laser diffraction method of GB / T19077-2016, and using a laser particle size analyzer (such as Mastersizer 2000E laser particle size analyzer) for measurement.

[0148] The parameter settings and performance test results of each embodiment and each comparative example are shown in Table 1.

[0149] Table 1

[0150]

[0151]

[0152]

[0153] The percentage of lithium supplement refers to the percentage of the total mass of the first active substance and the lithium supplement. The mass percentage of particles with the first particle size refers to the mass percentage of particles with the first particle size in the second active substance, and the mass percentage of particles with the second particle size refers to the mass percentage of particles with the second particle size in the second active substance.

[0154] 3. Preparation of secondary batteries

[0155] 1. Preparation of negative electrode

[0156] Artificial graphite, conductive carbon black, binder carboxymethyl cellulose (CMC) and solvent water are uniformly mixed in a weight ratio of 94:3:3:100, and stirred to obtain a uniform negative electrode slurry; the negative electrode slurry is uniformly coated on a 6μm thick copper foil current collector, the coating thickness is about 160μm and then dried at 100°C. After a cold pressing process with a pressure of 20-40 tons, a membrane with a coating thickness of about 100μm can be obtained.

[0157] 2. Preparation of Electrolyte

[0158] Ethylene carbonate (EC), polycarbonate (PC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:1:1, and then LiPF 6 is uniformly dissolved in the above solution to obtain an electrolyte. In the electrolyte, LiPF 6 The concentration is 1 mol / L.

[0159] 3. Diaphragm: A polyethylene film (PE) with a thickness of 12 μm is used as the separator.

[0160] 4. Preparation of Secondary Batteries

[0161] The positive electrode sheets, separators, and negative electrode sheets in the above-mentioned embodiments or comparative examples are stacked and wound in order to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the above-prepared electrolyte is added. After packaging, standing, forming, aging and other processes, a secondary battery is obtained.

[0162] 4. Secondary battery performance test

[0163] 1. Calculation of battery mass energy density

[0164] The weight M of all active materials loaded per unit area of ​​the positive electrode sheet of the secondary battery in each of the above embodiments and comparative examples was measured respectively. Each battery was charged at a rate of 0.33C to a voltage of 4.25V at room temperature, and then discharged at a rate of 0.33C to a voltage of 2.5V, and the discharge energy S0 was measured. The battery mass energy density calculation formula is as follows:

[0165] Battery mass energy density = S0 / M

[0166] 2. Battery discharge rate performance test

[0167] Five secondary batteries in each of the above embodiments and comparative examples were respectively tested in parallel. Each battery was charged at a rate of 0.33C at room temperature until the voltage was equal to 4.25V, and then discharged at a rate of 0.33C until the voltage was equal to 2.5V. The reversible energy was measured to be E0. Each battery was then charged at a rate of 0.33C at room temperature until the voltage was equal to 4.25V, and then discharged at a rate of 2.0C until the voltage was equal to 2.5V. The reversible energy was measured to be E1. The rate performance calculation formula is: rate performance (2C vs. 0.33C) = E1 / E0 × 100%. The greater the rate performance, the better the ion diffusion kinetics of the secondary battery.

[0168] 3. DC resistance test

[0169] At room temperature, the secondary batteries in the above embodiments and comparative examples are charged to the upper limit voltage at 1 / 3C rate, i.e., 100% SOC, and then the lithium-ion battery is discharged to 50% SOC, and after standing for 5 minutes, it is charged at 2C rate for 10 seconds to obtain the charging DCR of the lithium-ion battery at 50% SOC at room temperature. The smaller the charging DCR, the better the ion diffusion kinetics of the secondary battery.

[0170] It should be noted that the DC resistance DCR of the secondary battery is different from the resistance of the first active material layer and the second active material layer of the positive electrode sheet. The DC resistance DCR refers to the charging-related parameter of the secondary battery, and R1 and R2 represent the physical properties of the first active material layer and the second active material layer, respectively.

[0171] 4. Determination of the porosity of the first active material layer

[0172] Disassemble the secondary batteries in each of the above-mentioned embodiments and comparative examples respectively to obtain the positive electrode plates after formation, scrape off the second active material layer of the plates, take the plates coated with the first active material layer, use a punching machine to punch out small discs with a diameter of 14 mm, and use tweezers to select more than 20 discs with good appearance and no powder falling on the edges and put them into the sample cup. Record the number of discs and calculate the apparent volume V2. Place the sample cup containing the discs in a true density tester and a closed test system, introduce helium according to the procedure, detect the pressure of the gas in the sample chamber and the expansion chamber, and then calculate the real volume V1 according to Bohr's law (PV=nRT), thereby obtaining the porosity of the sample to be tested. Porosity P=(V2-V1) / V2*100%, apparent volume V2=S*H*A;

[0173] Where S represents the area, cm 2 ; H is the thickness, cm; A is the number of electrode discs; V1 is the actual volume of the disc, cm 3 ; V2 is the apparent volume of the electrode disc, cm 3 .

[0174] The secondary battery performance test results of each embodiment and comparative example are shown in Table 2.

[0175] Table 2

[0176]

[0177]

[0178] It can be seen from the results of Examples 1-33 and Comparative Examples 1-2 in Tables 1 and 2 that the electrode of the present application is provided with a double-layer active material layer, and by adding a lithium supplement in the first active material layer located on the surface of the current collector to increase the porosity in the first active material layer, and the second active material layer away from the current collector has a high compaction density, which increases the energy density of the electrode while improving the ion diffusion kinetics of the electrode. The above-mentioned electrode is applied to secondary batteries to improve the energy density and ion diffusion kinetics of the secondary batteries. In particular, by further adjusting the amount of lithium supplement, particle size, thickness ratio of the first active material layer, particle size and amount of first particle size particles and second particle size particles in the second active material layer when preparing the electrode, the energy density and ion diffusion kinetics of the secondary battery using the electrode can be further improved.

[0179] The main difference between Examples 1-5 is that the amount of lithium supplement is different. The amount of lithium supplement in Example 4 is the largest, and the amount of lithium supplement in Example 5 is the smallest. The results of Examples 4 and 5 are worse than those of Examples 1 to 3. The technicians analyzed the reason. This may be because when the amount of lithium supplement is small, it is not possible to remove an appropriate amount of lithium ions and produce an appropriate amount of oxygen during the high voltage formation process; on the one hand, the ionic conductivity of the electrolyte is limited, which is not conducive to the migration of lithium ions into the electrode; on the other hand, it is not possible to form a suitable porosity in the first active material layer, which is not conducive to the infiltration of the electrolyte, and the electrode concentration polarization effect cannot be effectively reduced; therefore, when the amount of lithium supplement is small, the ion diffusion kinetics of the electrode and the secondary battery cannot be effectively improved. When the amount of lithium supplement is large, although the pores in the electrode increase significantly, the kinetics are significantly improved. However, too many pores will lead to energy density loss. For secondary batteries, both high kinetics and high energy density must be met, so the addition of lithium supplement needs to be controlled within a reasonable range.

[0180] The main difference between Example 1 and Examples 6-9 is that the volume average particle size Dv50 of the first particle size particles in the second active material is different. The volume average particle size Dv50 of the first particle size particles in Example 8 is the largest, and the volume average particle size Dv50 of the first particle size particles in Example 9 is the smallest. The results of Examples 8 and 9 are poorer than those of Examples 1 and Examples 6-7. Preferably, the volume average particle size Dv50 of the first particle size particles satisfies: 10μm≤D1≤20μm, which can further improve the energy density and ion diffusion kinetics of the secondary battery.

[0181] The main difference between Example 1 and Examples 10-12 is that the volume average particle size Dv50 of the second particle size particles in the second active material layer is different. The volume average particle size Dv50 of the second particle size particles in Example 12 is the largest, and the result of Example 12 is poorer than the results of Examples 1 and Examples 10-11. Preferably, the volume average particle size Dv50 of the second particle size particles satisfies: 0.5 μm ≤ D2 < 10 μm, which can further improve the energy density and ion diffusion kinetics of the secondary battery.

[0182] The main difference between Example 1 and Examples 13-16 is that the mass proportions of the first particle size particles and the second particle size particles in the second active material layer are different. Preferably, in the second active material layer, the mass proportion of the first particle size particles is 60% to 90%, and the mass proportion of the second particle size particles is 10% to 40%, which can further improve the energy density and ion diffusion kinetics of the secondary battery.

[0183] The main difference between Example 1 and Examples 17-20 is that the ratio of the thickness of the first active material layer to the total thickness of the first active material layer and the second active material layer is different. The thickness of the first active material layer in Example 19 accounts for the largest proportion, and the thickness of the first active material layer in Example 20 accounts for the smallest proportion. The results of Examples 19 and 20 are worse than those of Examples 1 and 17-18. The technicians analyzed the reason, which may be due to the introduction of lithium supplements into the first active material layer to achieve pore formation. The content of the lithium supplement is proportional to the total mass of the first active material layer. The higher the thickness of the first active material layer, the greater the total mass of the first active material layer, and thus the higher the overall amount of lithium supplements added, the greater the porosity of the first active material layer, and the improved kinetics of the secondary battery; however, the lower the thickness of the second active material layer, the lower the energy density of the secondary battery. Therefore, the thickness ratio of the first active material layer is a key parameter.

[0184] The main difference between Example 1 and Examples 30-33 is that the volume average particle size Dv50 of the lithium supplement agent is different. The volume average particle size Dv50 of the lithium supplement agent in Example 32 is the smallest, and the volume average particle size Dv50 of the lithium supplement agent in Example 33 is the largest. The results of Examples 32-33 are worse than those of Examples 1 and Examples 30-31. The technicians analyzed the reason and found that it may be because when the amount of lithium supplement agent added is constant, the smaller the volume average particle size Dv50 of the lithium supplement agent, indicating that the weight of a single particle of the lithium supplement agent is lower, the more the number of lithium supplement agent particles, the more uniform the pores formed after the secondary battery is formed, and the more conducive to improving the dynamics of the secondary battery.

[0185] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0186] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. An electrode, characterized in that: include: current collector; A first active material layer, located on at least one surface of the current collector, wherein the porosity of the first active material layer is 15% to 50%, and the pores in the first active material layer are formed by a lithium supplement; The second active material layer is located on the surface of the first active material layer away from the current collector, the compaction density of the second active material layer is 2.2 g / cc to 3.7 g / cc, and the porosity of the second active material layer is 5% to 20%.

2. The electrode according to claim 1, characterized in that The resistance of the first active material layer is denoted as R1, and the resistance of the second active material layer is denoted as R2, then 1.0≤R1 / R2≤3.

0.

3. The electrode according to claim 2, characterized in that The resistance of the first active material layer satisfies: 0.8Ω≤R1≤3.0Ω, and the resistance of the second active material layer satisfies: 0.3Ω≤R2≤1.0Ω.

4. The electrode according to claim 1, characterized in that The second active material layer includes a second active material, and the second active material includes particles of a first particle size and particles of a second particle size. The volume average particle size Dv50 of the particles of the first particle size is denoted as D1, and the volume average particle size Dv50 of the particles of the second particle size is denoted as D2. Then the volume average particle size Dv50 of the particles of the first particle size satisfies: 10μm≤D1≤20μm, and the volume average particle size Dv50 of the particles of the second particle size satisfies: 0.5μm≤D2<10μm.

5. The electrode according to claim 4, characterized in that The mass proportion of the particles with the first particle size in the second active material is 60% to 90%, and the mass proportion of the particles with the second particle size in the second active material is 10% to 40%.

6. The electrode according to any one of claims 4 to 5, characterized in that The second active material includes one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes and graphene.

7. The electrode according to any one of claims 1 to 5, characterized in that The total thickness of the first active material layer and the second active material layer is 80 to 300 μm.

8. The electrode according to claim 7, characterized in that The thickness of the first active material layer accounts for 10% to 60% of the total thickness of the first active material layer and the second active material layer.

9. The electrode according to any one of claims 1 to 5, characterized in that The lithium supplement includes one or more of lithium oxide, lithium superoxide and lithium-rich transition metal oxide.

10. The electrode according to claim 9, characterized in that The lithium-rich transition metal oxide includes one or more of Li2NiO2, Li5FeO4, Li2MnO3, Li6CoO4, Li6MnO4 and Li6ReO4.

11. A method for preparing an electrode according to any one of claims 1 to 10, characterized in that: The steps include: preparing a first slurry, wherein the first slurry includes a first active material and a lithium supplement; coating the lithium supplement agent on at least one surface of the current collector to form a first active material layer; A second slurry is prepared, and the second slurry is coated on a surface of the first active material layer away from the current collector to form a second active material layer.

12. The method for preparing an electrode according to claim 11, characterized in that: The added amount of the lithium supplement agent accounts for 1% to 10% of the total mass of the first active substance and the lithium supplement agent.

13. The method for preparing an electrode according to any one of claims 11 to 12, characterized in that: The volume average particle size Dv50 of the first active material is recorded as D3, and the volume average particle size Dv50 of the lithium supplement is recorded as D4. Then the volume average particle size Dv50 of the first active material satisfies: 0.5μm≤D3≤20μm, and the volume average particle size Dv50 of the lithium supplement satisfies: 1μm≤D4≤10μm.

14. The method for preparing an electrode according to any one of claims 11 to 12, characterized in that: The lithium supplement includes one or more of lithium oxide, lithium superoxide and lithium-rich transition metal oxide.

15. The method for preparing an electrode according to claim 14, characterized in that: The lithium-rich transition metal oxide includes one or more of Li2NiO2, Li5FeO4, Li2MnO3, Li6CoO4, Li6MnO4 and Li6ReO4.

16. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate is the electrode according to any one of claims 1 to 10 or the electrode prepared by the method according to any one of claims 11 to 15.

17. A battery module, characterized in that: Includes the secondary battery as claimed in claim 16.

18. A battery pack, characterized in that: Comprising the battery module as claimed in claim 17.

19. An electrical device, characterized in that: It includes one or more of the secondary battery according to claim 16, the battery module according to claim 17, and the battery pack according to claim 18.

Citation Information

Patent Citations

  • Electrochemical device and electronic device

    CN113078288A

  • Secondary battery and preparation method thereof, and battery module, battery pack and device comprising secondary battery

    CN114730910A